EFFECTIVENESS OF HIDDEN MESSAGES IN ADVERTISEMENTS TOWARDS VIEWERS’ BUYING INTENTION - Omar, Nurul Nisa; Yee, Tan Mun (PEOPLE: International Journal of Social Sciences, 2017)
Advertisements are generally used to deliver messages to inform, remind or persuade; in hopes that it could influence viewers’ future actions. It is common for the style of the message delivered in advertisement contains double-meaning or multi-layered statement in which it compromises hidden messages for viewers to gauge. This article discusses the effectiveness of hidden messages in advertisement towards viewers’ buying intention. It is based on the case study of well-known TV commercial by the Malaysian telecommunication service provider that uses competitive hidden messages style of advertising. This study uses content analysis and surveys questionnaires for the data collection procedures. Results from the findings discuss the depth of hidden messages that occurs in the advertisement together with viewers’ insight on the effect the advertisement has towards their buying intention. The outcome of this paper is beneficial to enhance the application of effective advertising language that can be practiced in current advertising and media industry.